Incidence and Risk Factors for Postpartum Severe Hypertension in Women with Underlying Chronic Hypertension - Glover, Angelica V.; Tita, Alan; Biggio, Joseph R.; Anderson, Sarah B.; Harper, Lorie M. (American Journal of Perinatology, 2019)
Objective To determine risk factors and time to diagnosis of postpartum severe hypertension (PHTN) in women with chronic hypertension (CHTN).Study Design Retrospective cohort of singleton pregnancies with CHTN at a tertiary care center. The primary outcome was PHTN, defined as hypertension ≥160/ ≥ 110 mm Hg during an emergency room (ER) or outpatient visit, or hospitalization within 8 weeks postpartum. Multivariable logistic regression was used to assess independent risk factors for PHTN.Results Two-hundred thirty-five women had CHTN: 30 (12.8%) were diagnosed with PHTN, and 17 (7.2%) were hospitalized or seen in the ER for PHTN. Women with PHTN had more severe superimposed pre-eclampsia (p < 0.05), higher average systolic blood pressures at discharge (141 vs. 135 mm Hg, p = 0.04), and required antihypertensives after delivery (p < 0.01). The number of antihypertensive medications (adjusted odds ratio [aOR] 1.78, 95% confidence interval [CI], 1.25–2.55) and a systolic blood pressure >135 mm Hg (aOR 4.55, 95% CI, 1.64–12.61) at discharge remained independently associated with PHTN. Median time to diagnosis of PHTN was 10 days (interquartile range [IQR] 6–32 days); time to diagnosis among women requiring readmission or ER evaluation was 8 days (IQR 5–11 days).Conclusion PHTN occurred in 13% of women with CHTN, and was associated with blood pressure level and number of medications at discharge.
Keywords: chronic hypertension; postpartum; severe hypertension